Prospective Directions of Financial Market Development in Uzbekistan - Jo’rayev Og’abek (Genius Journals, 2023)
The role and importance of the financial market in the country's economy, its main trends in the future are widely explained in the article. In the context of the development of the financial market, prospects for improving the activity of the Uzbekistan Stock Exchange were considered.
Keywords: financial market; financial instruments; stock exchange; market capitalization